2017
DOI: 10.1016/j.tins.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Sleeping Cerebellum

Abstract: We sleep almost one-third of our lives and sleep plays an important role in critical brain functions like memory formation and consolidation. The role of sleep in cerebellar processing, however, constitutes an enigma in the field of neuroscience; we know little about cerebellar sleep-physiology, cerebro-cerebellar interactions during sleep, or the contributions of sleep to cerebellum-dependent memory consolidation. Likewise, we do not understand why cerebellar malfunction can lead to changes in the sleep-wake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 151 publications
(174 reference statements)
4
105
0
1
Order By: Relevance
“…Nevertheless, the mechanism and functional meaning of cerebellar recruitment during cortical slow oscillations is still to be fully understood. One intriguing possibility is that changes in cerebellar activity play a role in the consolidation of motor memories, and possibly of other cognitive skills (Canto et al, 2017). In line with this view, here we found that portions of the cerebellum activated during sleep slow waves especially include those connected with the somatomotor network and, to a lesser extent, to the spatially close frontoparietal and ventralattention networks.…”
Section: Cerebellar Involvement In Human Sleep Slow Wavessupporting
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, the mechanism and functional meaning of cerebellar recruitment during cortical slow oscillations is still to be fully understood. One intriguing possibility is that changes in cerebellar activity play a role in the consolidation of motor memories, and possibly of other cognitive skills (Canto et al, 2017). In line with this view, here we found that portions of the cerebellum activated during sleep slow waves especially include those connected with the somatomotor network and, to a lesser extent, to the spatially close frontoparietal and ventralattention networks.…”
Section: Cerebellar Involvement In Human Sleep Slow Wavessupporting
confidence: 87%
“…Changes in cerebellar activity have been previously reported as a function of sleep stage as well as in association with the occurrence of sleep slow waves (for a detailed review see Canto et al, 2017). Yet, the determinants of sleep-dependent changes in cerebellar activity and the possible role of the cerebellum in sleep regulation are still largely unknown.…”
Section: Cerebellar Involvement In Sleep Slow Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to cerebellar synaptic function, we cannot rule out that deficits in synaptic transmission to Purkinje cells may contribute to the motor function delay of the patients, but it is worth noting that no obvious motor deficits were observed in the Gria3 A653T mice, although specific tests were not performed. Intriguingly, impaired cerebellar function has been linked to sleep deficits (reviewed in ( 45 )) which might point to a direct link between the impaired cerebellar synaptic transmission and the sleep phenotype observed.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue enrichment analyses of gene expression from GTEx tissues identified enrichment of associated genes in several brain regions including the cerebellum, a region of emerging importance in sleep/wake regulation 43 , frontal cortex, anterior cingulated cortex, nucleus accumbens, caudate nucleus, hippocampus, hypothalamus, putamen, and amygdala ( Figure 2c, Supplementary Table 25 ). Enrichment was also observed in the pituitary gland.…”
mentioning
confidence: 99%